Improvement of the mathematical model of singlephase halfbridge inverter in statevariable form - Vasylets, Sviatoslav; Vasylets, Kateryna (Eastern-European Journal of Enterprise Technologies, 2018)
The mathematical model of the insulated-gate bipolar transistor in the IGBT module is improved due to the determination of analytical expressions for dynamic spurious capacitances of the device. The expressions are obtained by analytical differentiation of functions that approximate the dependence of the spurious capacitances of the transistor on the voltage between the collector and the emitter. The method of forming a mathematical model of the IGBT voltage inverter in the form of matrix differential equations of state in the Cauchy form and nonlinear equations is proposed. There are no restrictions on the number of transistors and the configuration of the circuit. The method is based on the matrix-topological method of electrical circuits analyzing. The application of this method is illustrated by the example of a single-phase half-bridge inverter with resistive load. The urgency of improving the mathematical model of the IGBT inverter is caused by the need to analyze the electrical safety of the state of the variable frequency circuit between the frequency converter and the motor. Existing models of frequency-controlled electric drives do not take into account a number of factors that significantly affect the accuracy of the simulation. Such factors include the dynamic nature of the IGBT spurious capacitances and the disconnection of one of the machine phases from the network during the dead time when switching adjacent power switches of the inverter. The obtained mathematical model differs from the well-known in advanced representation of separate elements by nonlinear differential equations and taking into account mutual influences. The proposed approach allows to investigate the high-frequency transient components of currents and voltages in electrical systems with semiconductor converters. This simplifies taking into account the recharging processes of the IGBT capacitances during a dead time when switching adjacent power switches in the model. The peculiarities of the IGBT inverter switching transients are revealed, in particular, the significant exceeding, more than twice, of the transistor current during opening the operating current at the end of the switching process.